Implementasi Media Pembelajaran Interaktif Berbasis Animasi Materi Waktu pada Siswa SD - Nita Hidayati; Lessa Roesdiana; Betha Nurina Sari (IKIP PGRI Bojonegoro, 2021)
Pandemic of Covid-19 has a major impact in various sectors, one of which is the education sector. The educators must make sure that teaching and learning activities are still running, even though students are at home. The solution, educators are required to design learning media as an innovation by utilizing online media. Information technology-based learning media can train students' independence. One of them is animation interactive learning media. From the idea of these problems, we shall conduct training on the preparation of animation-based interactive learning media for primary school teachers in Karawang District. the strategy used is that the method of approach and method of implementation. The target output of this activity is to extend the mastery and skills of teachers within the preparation of instructional media. The results of this training is that the addition of recent knowledge for the teacher within the preparation of instructional media, so that this knowledge can make it easier for students in learning mathematics. Pandemi Covid-19 berdampak besar pada berbagai sektor, salah satunya pendidikan. Pendidik harus memastikan kegiatan belajar mengajar tetap berjalan, meskipun peserta didik berada di rumah. Solusinya, pendidik dituntut mendesain media pembelajaran sebagai inovasi dengan memanfaatkan media daring (online). Media pembelajaran berbasis teknologi informasi dapat melatih kemandirian siswa. Salah satunya adalah media pembelajaran interaktif animasi. Atas dasar permasalahan tersebut kami bermaksud akan mengadakan pelatihan penyusunan media pembelajaran interaktif berbasis animasi bagi guru SD di kabupaten karawang. Metode yang digunakan adalah metode pendekatan dan metode pelaksanaan. Target luaran dari kegiatan ini adalah: menambah penguasaan dan keterampilan guru dalam penyusunan media pembelajaran. Hasil dari pelatihan ini adalah adanya penambahan pengetahuan baru bagi guru dalam penyusunan media pembelajaran, yang mana dengan pengetahuan ini dapat mempermudah siswa dalam pembelajaran matematika.